Rural Labor Mobility in the Process of Industrialization under Triple Dimensions: Time, Space, and People - Li, Cheng (Latin American Journal of Trade Policy, 2020)
Rural-to-urban labor migration in developing economies, if beyond employment absorption capacity, is both a symptom of underdevelopment and the factor that exacerbates underdevelopment. Although various theories in development economics, in particular, the dual economy, together with numerous migration literature, bore intention to explore a balanced development approach in rural labor mobility, content-based studies are often overwhelmed, whereas the context/circumstance-based angle (like industrialization) in the research of labor mobility is always neglected. This paper reviews, under an ancient Chinese epistemological methodology that consists of time, space, and people, labor mobnility theories. It combines the old institutionalist and new structuralist schools of thought, searching a dynamic theoretical framework to deconstruct the overarching labor mobility in the process of industrialization.